The Influence Of Strategic Orientation And Competitive Advantage On Export Performance: A Study Among The Manufacturing Smes In Malaysia - Zainal Abidin, Nurul Illahi (2024)
The objectives of this study, data is obtained from the top management of SMEs in the manufacturing industry operating in the Malaysian Peninsular. The SMEs are owned by a sole-proprietor, partnership and private limited who has experience in international markets as certified by the Federation of Malaysian Manufacturers Agency and the Malaysian Foreign Trade Development Association.